Amber Outskirts - (:unkn) unknown (My University, 2018)
Amber Outskirts opens with 25-year-old Penelope Moore searching for the girl she once loved, Amber, who disappeared after they shared a drug-fuelled night. Penny finds Amber in a gritty town in rural New South Wales where she is every bit as wild, but now married to a brutal man, Pete. There’s no room for Penny in Amber’s new life, but Penny can’t stay away. Penny gets a job at the local orchard, where Amber works, and it’s not long before she’s invited to a party where there’s a muddle of drink and desire. By the night’s end, Pete slips away with a lover and in an act of revenge Amber sleeps with his brother, Angus. The following morning, Penny wakes hungover—and lost—in the bush. Trying to find her car, she stumbles on Amber in a remote clearing. Amber is acting strangely, and asks Penny if she’ll drive the Kombi. Penny follows her instructions to reverse, and hits a body; it turns out Pete was sleeping behind the vehicle. On seeing Pete rolling in agony, Penny realises Amber intended for her to hit Pete’s lover. With Pete hospitalised, the women escape cross-country. Amber attempts to see her incarcerated mum for guidance, but her mum refuses her visit. Devastated by the rejection, Amber spins into a manic state, insisting they return to Penny’s childhood home. Together, they break into the Bondi mansion, only for a neighbour to alert the cops. Faced with being arrested, Penny is forced to contact her mum to prove she has a right to be on the premises. Her mum rushes home to find her weary daughter, who admits to running a man over and voluntarily goes to the police station to testify. A year later, Penny is working as a barista in Sydney, having been fully acquitted, and coping with the emotional impact of the court case. Amber has been sentenced to twelve years in prison and has cut off communication with Penny. Penny’s decides to return to Shearsend, where she is determined to resurrect her father’s childhood orchard. At the orchard, Penny hikes up a mountain and from her lookout sees a van pause at the end of her driveway. Approaching her mailbox, she hopes for a letter from Amber.